Emplacement modes of the Ladinian plutonic rocks of the Dolomites: Insights from anisotropy of magnetic susceptibility. (August 2018) - Abbas, Hassan; Michail, Maria; Cifelli, Francesca; Mattei, Massimo; Gianolla, Piero; Lustrino, Michele; Carminati, Eugenio
Abstract: In the Dolomites (Eastern Southern Alps, Italy), a diffuse Middle Triassic igneous activity is now present mostly as lava flow and pyroclastic successions, with rare shallow-depth intrusive bodies cropping out at Predazzo, Monzoni and Cima Pape areas. In this work, the emplacement modes of the Predazzo and Monzoni bodies were investigated by means of petrographic and anisotropy of magnetic susceptibility (AMS) data coupled with a field geological study. The presence of intrusive rocks in between these two bodies and the continuity of the metamorphic aureola from west of the Predazzo to east of the Monzoni body suggest that they are parts of a ∼20 km wide SW-NE oriented continuous pluton, sub-parallel to Ladinian strike-slip faults. AMS and petrographic data from the Predazzo body are consistent with a multistage ring-dyke emplacement mode, with areas of upward flow of the magma located in the NW and ESE part of the intrusion, whereas in the southern sector of the pluton our data suggest prevalently horizontal flows. In general, the Predazzo sheets indicate either upward magma flow or along-strike lateral magma transport, and the round shape suggests no influence of Ladinian tectonic structures. On the contrary, the ENE-WSW elongated shape of the Monzoni body was controlled by the occurrence of strike-slip faults associated with Ladinian-tectonics, the feeder being likely located at the NE edge of the body. However, the absence of deformation at the field- and micro-scale is consistent with a post Ladinian-tectonics timing of emplacement, as for the Predazzo pluton. Highlights: Emplacement of Triassic Predazzo and Monzoni plutons (Dolomites) is investigated. Petrographic and anisotropy of magnetic susceptibility (AMS) data are used. Middle Triassic structures controlled plutons emplacement modes. Predazzo body was emplaced as a multistage ring-dyke complex. Monzoni emplacement was controlled by a Ladinian strike-slip fault.